2018
DOI: 10.1016/j.semarthrit.2017.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare utilization and expenditures for United States Medicare beneficiaries with systemic vasculitis

Abstract: The average Medicare beneficiary with SV incurs about double the annual healthcare expenditures compared to their non-SV counterparts, attributable to increased utilization of almost all categories of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Systemic vasculitis, including AAV, is associated with increased healthcare costs due to increases in hospital care and expensive medications [ 4 , 38 , 39 ]. Biological therapies used for relapsing AAV cost in excess of £6000 annually per patient.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic vasculitis, including AAV, is associated with increased healthcare costs due to increases in hospital care and expensive medications [ 4 , 38 , 39 ]. Biological therapies used for relapsing AAV cost in excess of £6000 annually per patient.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic lupus erythematosus (ICD‐9: 710.0 or ICD‐10: M32.1) was defined by ≥3 inpatient or outpatient diagnoses, each at least 30 days apart 19 . Morphoea (ICD‐9: 701.0 or ICD‐10: L94.0, L94.1, L94.3), systemic sclerosis (ICD‐9: 710.1 or ICD‐10 M34.x), Sjogren’s syndrome (ICD‐9: 710.2 or ICD‐10: M35.0x) and systemic vasculitis (ICD‐9: 446.5, 446.7, 446.0, 446.1, 446.4, 287.0, 446.21, 447.6 or ICD‐10: M30.0, M30.1, M31.x or ICD‐10: M31.5, M31.6, M31.4, M30.0, M31.3x, M30.1, D69.0, M31.0, M31.7) were each defined by ≥1 inpatient diagnosis or ≥2 outpatient diagnoses at least 60 days apart but within 2 years or ≥1 diagnosis by a rheumatologist 20–22 . The event date is the date on which all criteria are fulfilled.…”
Section: Methodsmentioning
confidence: 99%
“…There are limited and variable data about the economic burden of systemic vasculitis on healthcare systems [ 11 ]. Thorpe et al reported that in the year 2010 in the USA, patients with systemic vasculitis had about double the annual healthcare expenditures compared to their non-vasculitis counterparts [ 12 ]. Babigumira et al reported that the US patients with a new GCA diagnosis had substantially higher health care costs compared to the patients without GCA; the difference in 1-year cost was $16,431 (95% CI $13,821–$19,041) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%